IL-1α reversibly inhibits skeletal muscle ryanodine receptor a novel mechanism for critical illness myopathy? - Edwards, Joshua N.; Weber, Cornelia; Liu, Ilon; Reischl, Barbara; Most, Patrick; Wirth-Hücking, Anette; Yi, Bing; Friedrich, Oliver; Voelkers, Mirko; Buttgereit, Andreas; Lang, Roland; Lee, Aven; et al. (American journal of respiratory cell and molecular biology, 2014)
Critical illness myopathies in patients with sepsis or sustained mechanical ventilation prolong intensive care treatment and threaten both patients and health budgets; no specific therapy is available. Underlying pathophysiological mechanisms are still patchy. We characterized IL-1α action on muscle performance in "skinned" muscle fibers using force transducers and confocal Ca fluorescence microscopy for force/Ca transients and Ca sparks. Association of IL-1α with sarcoplasmic reticulum (SR) release channel, ryanodine receptor (RyR) 1, was investigated with coimmunoprecipitation and confocal immunofluorescence colocalization. Membrane integrity was studied in single, intact fibers challenged with IL-1α. IL-1α reversibly stabilized Mg inhibition of Ca release. Low Mg-induced force and Ca transients were reversibly abolished by IL-1a. At normal Mg , IL-1α reversibly increased caffeine-induced force and Ca transients. IL-1α reduced SR Ca leak via RyR1, as judged by (1) increased SR Ca retention, (2) increased IL-1α force transients being reproduced by 25 μM tetracaine, and (3) reduced Ca spark frequencies by IL-1a or tetracaine. Coimmunoprecipitation confirmed RyR1/IL-1 association. RyR1/IL-1 immunofluorescence patterns perfectly colocalized. Long-term, 8-hour IL-1α challenge of intact muscle fibers compromised membrane integrity in approximately 50% of fibers, and confirmed intracellular IL-1α deposition. IL-1α exerts a novel, specific, and reversible interaction mechanism with the skeletal muscle RyR1 macromolecular release complex without the need to act via its membrane IL-1 receptor, as IL-1R membrane expression levels were not detectable in Western blots or immunostaining of single fibers. We present a potential explanation of how the inflammatory mediator, IL-1α, may contribute to muscle weakness in critical illness. Copyright © 2014 by the American Thoracic Society.
Keywords: Critical illness myopathy; Cytokines; IL-1; Ryanodine receptor 1